Trans Rights: The Ongoing Debate in Latin American Legal Agendas - López Hidalgo, Sebastián (The Age of Human Rights Journal, 2022)
This article offers an overview of the Trans people’s rights agenda in Latin America. It focuses on various Latin American countries to reveal how the route towards rights has been marked by a binary and medicalizing approach to non-normative identities, directly influenced by the traditional and conservative moral projects prevalent in the region. It also accounts for some recent normative and case-law developments, which however coexist with restrictive norms that criminalize the rights of gender-diverse people. It concludes that the recognition of Trans people’s rights is often insufficient, that it contributes to rendering Trans diverse realities invisible, thus reinforcing discrimination.